Corporate Social Responsibility (CSR) From Islamic Perspective: A Literature Discussion - Mohd Shukor Harun; Muhamad Fikri Aziz; Razli Ramli (Asian Scholars Network, 2024)
Volume: 8 Issues: 59 [December, 2023] pp. 125 - 137